Engineer's Roll in Sustainable Recovery Process of Post (Natural) Disaster’. Proceedings of International Conference on Contemporary Management - Sivakumar, S. (Faculty of Management Study, University of Jaffna Publication, 2014)
This article reveals that the different aspect of sustainable recovery process, where engineers should have played a different and profound professional roll in post tsunami development process. Unfortunately, our beloved country, which all this time was spared by calamities of this magnitude, ultimately had to face the savage judgement of nature. The ravaging waves not only engulfed valuable lives of our very own but also brought down everything we had built in our coastal towns over the centuries in the blink of an eye the tsunami disaster has deeply affected the lives of the families living throughout the coastal belts of the country causing to be disrupted both by the damage to infrastructure and facilities for livelihood, as well as the disruption in the family structure and displacement of families. In addition to the negative impact, the tsunami has had on the livelihood support infrastructure in the 65% of the tsunami affected areas of Sri Lanka is also struggling to recover from three decades of civil war. The prolonged conflict, coupled with the impact of the tsunami has not only affected the livelihood support infrastructure, but the most of the other infrastructures as well. Hence the engineers are having the profound professional responsibilities to first to recover the damage caused by the natural disaster, then by rehabilitating/re-constructuring the damaged facilities. The final task to the engineers must be to support sustainable development activities to improve the socio economic status of the disaster affected community. The strategy spelled out in this article will be common for even post war recovery process also.
Keywords: tsunami